2016
DOI: 10.1002/slct.201601043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Molecular Polarizability in Designing Organic Piezoelectric Materials

Abstract: Nowadays, piezoelectric materials have found various applications in fields like energy harvesting, precision mechanics and life sciences. In this regard organic molecules and their crystals are not explored in detail to be used as an alternative source for piezoelectric materials. Piezo‐coefficients of different H‐bond cluster were calculated. It was found that Sulfur Centered Hydrogen Bond (SCHB) complexes have the optimum hydrogen bond strength and dipole moment derivative for achieving maximum piezo‐respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The reduced Polaris ability of the amide bond could therefore also result in the observed decrease in shear piezoelectricity. 42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced Polaris ability of the amide bond could therefore also result in the observed decrease in shear piezoelectricity. 42 …”
Section: Discussionmentioning
confidence: 99%
“…The reduced polarisability of the amide bond could therefore also result in the observed decrease in shear piezoelectricity. 42 PFM images of soluble collagen films reveal worm-like structures which possess topographical correlation with the lateral amplitude and inphase of the piezoelectric response, unlike its insoluble collagen counterpart. This indicates that although the origin of piezoelectricity may be attributed to the ordering and charge imbalance of tropocollagen molecules, the large piezoelectric domains as observed in tendon 11 may be promoted by the crosslinking of the fibrils into large ordered structures.…”
Section: Piezoelectric Domains In Collagenmentioning
confidence: 94%
“…In organic crystals, the collective responses of hydrogen bonds and C-HÁ Á Á interactions to the applied electric field decide the piezoelectric behaviour of the grown crystal. For the design of highly piezoelectric organic materials, both the dipole moment and the polarizability of hydrogen-bonded systems need to be considered carefully (Gagrai et al, 2016). In hydrogenbonding systems, a bond or vibration mode with low force constant and a large change in dipole moment with a change in bond length are required for a large piezoelectric effect (Werling et al, 2014).…”
Section: Piezoelectricitymentioning
confidence: 99%
“…Moreover, theoretical calculations have revealed that the presence of hydrogen bonding plays a significant role in achieving a larger maximum piezo-response. [17] Indeed, organic materials with numerous hydrogen bonds in their molecular packing can potentially be efficient organic piezomaterials for strengthening the piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%